PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PERUSAHAAN YANG MENGALAMI FINANCIAL DISTRESS - Ema Apriyanti; Mujino Mujino; Risal Rinofah (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
The purpose of this research is knowing an influence of corporate governance on companies experiencing financial distress. The indicator is used to measure corporate governance in this research are the board of director, independent commissioner, managerial ownership, and institutional ownership. While financial distress as dependent variable can be measured by Altman Z-Score. This research takes a sample in industrial sector manufacturing companies that registered on the Indonesia Stock Exchange (IDX) in 2014-2018. The sampling technique uses purposive sampling and fill the sample criteria. The sample is used in this research are 10 companies, so has obtained 50 samples researched. This research is tested by multiple regression linear analysis test. The result showes that simultaneous corporate governance variable significantly influenced on financial distress. The board of director has a significant positive influence on financial distress. Independent commissioners do not have a significant influence on financial distress. Managerial ownership and institutional ownership have a significant negative influence on financial distress.